Preparing for the Worst but Hoping for the Best: Censorship, Academic Libraries, and Reconsideration Policies - Solon, Blair; Montanez, Margie; Cooper, Liz; Jankowski, Amy; Koelling, Glenn; Soito, Laura (Library resources & technical services, 2025)
Libraries in the United States have received the highest number of book challenges on record in recent years. Although the vast majority of these challenges happened at school or public libraries, we sought to assess how academic libraries are prepared to face such challenges, especially with the rise of state laws seeking to limit what subjects can be taught. To answer this question, we analyzed American members of the Association of Research Libraries' reconsideration policies. Our analysis found that a minority of these libraries had a reconsideration policy. These policies varied in how they framed the potential challenge and the procedure to handle a removal request. The messages within these documents were mixed, often obscuring the actual policy. They relied on justifications, typically citing the purpose of an academic library and/or ethical statements from professional bodies, and they borrowed language from other institutions' policies. We conclude with recommendations for creating a reconsideration policy tailored for academic libraries.